Stabilisasi Tanah Lunak Menggunakan Lumpur Bledug Kuwu dan Larutan Asam Fosfat Ditinjau Dari Nilai Kuat Tekan Bebas - Winarno, Arief Budi; Syahril, S. (Institut Teknologi Bandung, 2024)
Abstract Soft soils with low bearing capacity are a major problem in construction that can lead to failures, such as road damage, building tilts, and bridge collapses. This research aims to improve the bearing capacity of soft soil in Gedebage, Bandung, using a soil stabilization method with Bledug Kuwu mud (LBK) and phosphoric acid solution (LAF). Bledug Kuwu mud was selected due to its chemical composition, which is similar to fly ash and volcanic ash, particularly in terms of SiO₂, Al₂O₃, and Fe₂O₃ content. Phosphoric acid, though rarely used in construction, was chosen for its potential as an effective soil stabilizing agent. The research methodology involved collecting native soil samples from Gedebage and conducting physical and mechanical property tests at the Geotechnical Laboratory of Bandung State Polytechnic. The test results indicated that the optimum mixture of 15% LBK and 10% LAF successfully reduced the soil's Plasticity Index (PI) by 73.91%, from 46% to 12%. In addition, the unconfined compressive strength (qu) increased by 35% compared to the native soil, with a qu value of 1.02 kg/cm² and cohesion (c) of 0.51 kg/cm², indicating an improvement in soil consistency to the